India’s New Cloud Computing Policy: Localization Of Data - Parul, Parul (International Journal of Computer Sciences and Engineering, 2025)
The rapid evolution of processing power, storage technologies and availability of high quality broadband speed and big data have enabled the realization of a new computing model called cloud computing. In cloud computing, resources such as computing power &infrastructure, application platforms, and business processes are provided through the internet as general utilities to users in an on demand fashion. Business enterprises are now increasingly seeking to reshape their business models to gain benefits from this new paradigm of resource sharing